ANALİSİS Pengaruh Work overload, Perceived Organizational Support, Interpersonal Conflict dengan mediasi organizational commitment terhadap OCB di Honda Ahass - Yuddy Giovanna Priscilla; Vanessa Hu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to determine whether there is a significant effect of work overload, perceived organizational support, interpersonal conflict and organizational commitment on organizational citizenship behavior at Honda Ahass. This study used 100 respondents from Honda Ahass employees using the saturated sampling formula method, namely only employee respondents in the 3 companies that I selected were respondents in this study. This study uses the SPSS version 26.0 program for analysis of respondents' demographic data and then continues with testing using the SmartPLS version 3.0 program for analysis of the relationship between variables. Based on the results of hypothesis testing, the data shows that interpersonal conflict, perceived organizational support has no significant effect on organizational commitment and organizational citizenship behavior, work overload has a significant effect on organizational citizenship behavior. Based on the results of this study, in increasing perceived organizational support for organizational citizenship behavior, the Honda Ahass employees are suggested to be able to increase organizational commitment first through the creation of perceived organizational support and organizational citizenship behavior